Perancangan Game Edukasi Sebagai Media Pelestarian Bahasa Gorontalo Pada Anak Sekolah Dasar - Moh. Rifandi R.M; Irma Surya Kumala Idris; Abd. Rahmat Karim Haba (Teknik Informatika Fakultas Ilmu Komputer Universitas Ichsan Gorontalo, 2023)
The learning process using conventional methods does not provide optimal learning outcomes. For optimal learning, the selection of the learning model is very important which is accompanied by the selection of the right learning media. The use of games as learning media is not wrong because games can indirectly provide education. Playing games without educational content may negatively impact children. To achieve optimal learning results, this research takes the initiative to make Gorontalo language educational games that can be played through smartphone media based on the Android operating system. In educational game design, there are two main features, namely the play menu and the learning menu. To be able to complete the game on the play menu, players must capture Gorontalo vocabulary words following the available vocabulary images. While in the learning feature players can learn the vocabulary available in the game. Based on the results of black box testing, the features contained in the Gorontalo Language Educational Game can run properly without any errors occurring. Meanwhile, based on user acceptance testing, the game that has been designed can be accepted by students with a total score of 90.5% in the Very Feasible category.